2020
DOI: 10.3390/jcm9010220
|View full text |Cite
|
Sign up to set email alerts
|

QFR Predicts the Incidence of Long-Term Adverse Events in Patients with Suspected CAD: Feasibility and Reproducibility of the Method

Abstract: AIMS: We evaluate feasibility and reproducibility of post hoc quantitative flow ratio (QFR) measurements and their prognostic predictive power during long-term follow-up. METHODS AND RESULTS: Between 2010 and 2012, 167 patients without angiographic evidence of significant stenoses were enrolled in a prospective registry. Of these patients, 96% presented 7 years follow-up data. QFR was measured post hoc by three certified investigators. QFR analysis was feasible in 71% of left anterior descending (LAD), 72% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In a previous study from our group, we demonstrated that QFR identifies hemodynamically relevant stenoses in about 10% of the patients who have undergone diagnostic coronary angiography and have been discharged with a diagnosis of intact coronaries. In the same study, we demonstrated that a QFR ≤ 0.80 was the strongest predictor of events (HR 3.14, 95%CI 1.78–5.54, p = 0.0001), an association which was maintained in several sensitivity analyses ( 37 ).…”
Section: Discussionmentioning
confidence: 64%
“…In a previous study from our group, we demonstrated that QFR identifies hemodynamically relevant stenoses in about 10% of the patients who have undergone diagnostic coronary angiography and have been discharged with a diagnosis of intact coronaries. In the same study, we demonstrated that a QFR ≤ 0.80 was the strongest predictor of events (HR 3.14, 95%CI 1.78–5.54, p = 0.0001), an association which was maintained in several sensitivity analyses ( 37 ).…”
Section: Discussionmentioning
confidence: 64%
“…FFR has many limitations in clinical practice. The use of QFR in the catheter laboratory is very feasible [17]. When computed by specialized technicians, the average QFR calculation time is only 4.36 ± 2.55 min [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, in a retrospective study of data collected by more than 50 centers, a weak correlation was reported between vFFR measurement and wire-based FFR measurement because of poor image quality and the difficulty tracking aortic pressure (30). The prognostic value of QFR measurements has been confirmed under various conditions (8,9,31), although the optimal cutoff values for post-PCI QFR measurements have been reported as 0.89, 0.91, and 0.80 in different studies. In the current singlecenter, retrospective study, patients with low post-PCI wirebased FFR (≤0.82) or caFFR (≤0.83) values were associated with a significantly higher risk of VOCE than those with high post-PCI FFR (>0.82) or caFFR (>0.83) values.…”
Section: Discussionmentioning
confidence: 99%